Marketing Strategies to Improve Consumer Purchasing Decisions - Solimah, Siti; Abidin, Zaenal; Nurjali (Zabags International Journal of Economy, 2025)
The research questions are: first, what is the marketing strategy for Asyifah's bitter melon chips? Second, what is the level of consumer purchasing decisions based on the marketing strategy for Asyifah's bitter melon chips? This research uses qualitative research with a descriptive approach. The research was conducted at Asyifah's bitter melon chips in Pandan Makmur Village. Data collection techniques were conducted through observation, interviews, and documentation methods related to the title. The data analysis techniques used were qualitative and descriptive analysis. Based on the discussion and analysis, the following conclusions were drawn: first, what is the marketing strategy for Asyifah's bitter melon chips? It focuses on the product itself, where the bitter melon chips offered by Asyifah are in high demand. Second, what is the level of consumer purchasing decisions based on the marketing strategy for Asyifah's bitter melon chips? Based on the marketing mix analysis, it can be said that there has been a significant increase in new customers, while the loyalty of existing customers remains stable.